Method for enhancing immune response of mammals by using electroporation device - XU JIANGLI; WANG XUDONG; WANG JUNYI; YANG PING; WANG YU; WANG WEIKUN; ZHANG HONGJUAN (2025)
The invention discloses a method for enhancing immune response of a mammal by using an electroporation device. The method comprises the following steps: injecting a vaccine composition to a first part tissue of the mammal for the first time; a second injection of the vaccine composition is then administered to a second site tissue of the mammal at a second time; and then a third injection of the vaccine composition is given to a third part tissue of the mammal at a third time. The invention provides a more efficient and stronger method for initiating immune response, and also provides a vaccine immunization mode with less damage to a subject. 本发明公开了一种利用电穿孔装置增强哺乳动物免疫反应的方法，包括在第一时间向所述哺乳动物的第一部位组织给予疫苗组合物第一次推注；接着在第二时间向所述哺乳动物的第二部位组织给予疫苗组合物第二次推注；然后在第三时间向所述哺乳动物的第三部位组织给予疫苗组合物第三次推注。本申请提供了一种更高效、更强的引发免疫反应的方法，同时也是一种对受试者损伤较小的疫苗免疫方式。